Population, distribution, and habitat of Bornean Elephant in Tulin Onsoi, Nunukan District, Indonesia based on dung counts - WISHNU SUKMANTORO; Agus Suyitno; Mulyadi Mulyadi; DONI GUNARYADI; AGANTO SENO; ALFRED INDRA KUSUMA; DARWIS DARWIS (Society for Indonesian Biodiversity, 2021)
Abstract. Sukmantoro W, Suyitno A, Mulyadi, Gunaryadi D, Seno A, Kusuma AI, Darwis. 2021. Population, distribution, and habitat of Bornean Elephant in Tulin Onsoi, Nunukan District, Indonesia based on dung counts. Biodiversitas 22: 311-319. The survey on population, distribution, and habitat of Bornean elephants is very important because it reduces the information gap about Bornean elephants’ population and distribution. In more detail, the study can be used for updating information and the needs of local government in a spatial plan based on biodiversity conservation. The survey of Bornean Elephant was conducted in Tulin Onsoi Subdistrict, Nunukan District, North Kalimantan Province, Indonesia, starting in February 2018 to May 2019. The survey area’s scopes are Agison, Sibuda, Apaan, and Tampilon sub-water catchment areas in 34 (5 x 5 km2) grids with a total of 850 km2.  The occupancy method with perpendicular line transect was used in this study. In the survey, the number of traces was 52 finding points with a total of 241 traces. The elephant dung identified in the dung piles (one-time defecation) was in 29 finding points with a total of 38 dung piles (0.22 dung piles per km). Based on Distance 6.0 and involved the formula of the elephant population’s density with standard defecation and dung decay ratio, the elephant population density in the Tulin Onsoi is between 4.8-5.7 individuals/100 km2. Minimum convex polygon (MCP)-qHull showed that the area of ??the elephant habitat is 253.12 km2 in Tulin Onsoi sub-district. Generally, the habitat conditions for the location are old secondary forests (37 %). Meanwhile, other habitats included in the survey area are primary forest, shrubs, and plantations, including community agriculture and roads. In the strategy of managing the Bornean elephant, efforts to stabilize or increase population are important things to do. Conservation-based spatial planning and close monitoring for the protection of small populations of this species and its threats, are options that can be selected for present and future in North Kalimantan.